FDY oil agent capable of directly oiling crude oil and preparation method thereof

By introducing phase change wear-resistant agents into FDY oil agents and using nano-silica-coated paraffin technology, the existing FDY oil agents have been solved under high temperature and wear conditions, and the wear resistance and high temperature resistance of the oil agents have been significantly improved.

CN119041058BActive Publication Date: 2025-03-21TONGXIANG HENGLONG CHEM CO LTD

Patent Information

Application Number
CN202411520641.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-03-21
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The existing FDY oil agents that can be directly oiled with crude oil have poor performance under high temperature and wear conditions, and have insufficient high temperature and wear resistance.

Method used

The phase change wear resistance and smoothing agent are mixed in a specific mass ratio by using a bundling agent, antistatic agent, emulsifier, phase change wear resistance and smoothing agent are prepared by an oil-in-water emulsification system. The wear resistance and high temperature resistance of the oil agent are improved by using nano-silica-coated paraffin.

Benefits of technology

The obtained FDY oil agent exhibits excellent wear resistance and high temperature resistance under high temperature and wear conditions, and has stable performance, is not easy to delaminate, and is suitable for long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides an FDY oil agent that can be directly oiled with crude oil and a preparation method thereof, the preparation method comprising: putting a sizing agent, an antistatic agent, an emulsifier, a phase change wear-resistant agent and a smoothing agent into a reactor; heating the reactor to 40°C to 60°C, turning on the stirring device of the reactor, and continuously stirring for 20min to 40min under heat preservation conditions to obtain the FDY oil agent; wherein the phase change wear-resistant agent is prepared by the following steps: using a raw material including paraffin to prepare an oil phase; using a raw material including ethyl orthosilicate to prepare an aqueous phase; using a raw material including polyol and isophorone diisocyanate, through an oil-in-water emulsification system, to prepare an emulsion; mixing the emulsion, the oil phase and the aqueous phase to prepare the phase change wear-resistant agent. The FDY oil agent of the present invention has good high temperature resistance and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile auxiliaries, in particular to an FDY oiling agent capable of directly oiling crude oil and a preparation method thereof. Background Art

[0002] Polyester is one of the synthetic fibers with the largest production capacity and the widest application in the world. Polyester is made of purified terephthalic acid (PTA) or dimethyl terephthalate (DMT) and ethylene glycol (MEG) as raw materials, and is made into fiber-forming polymer polyethylene terephthalate (PET) through esterification or transesterification and polycondensation reaction, and then PET is made into fiber through spinning and post-processing.

[0003] Since polyester does not have the natural gum and oil film of natural fibers, it has poor hygroscopicity and is not conductive. Therefore, static electricity is easily generated due to constant friction during the spinning process. Oil must be used to prevent or eliminate static electricity accumulation. At the same time, it gives polyester a soft and smooth property to enable it to pass through the subsequent processes smoothly.

[0004] FDY (Fully Drawn Yarn) oil that can be directly oiled with crude oil is also called crude oil type oil. Its function is to reduce the lint and broken ends in the high-speed spinning process, reduce the cost of the spinning process, save energy and improve product quality.

[0005] The main components of FDY oil, which can be directly oiled with crude oil, include sizing agents, antistatic agents, emulsifiers, lubricants, silicone oil and water. Its function is to adjust the friction between fibers and fibers, fibers and metals, improve the smoothness of the fiber surface and reduce the charge of the fibers; on the other hand, it increases the number of ions on the fiber surface, improves hygroscopicity, and allows the generated static electricity to dissipate quickly.

[0006] The FDY oil agent that can be directly oiled with crude oil in the prior art has the following disadvantages: the high temperature resistance and wear resistance of this type of FDY oil agent are not ideal. Summary of the invention

[0007] One of the problems solved by the present invention is how to provide an FDY oil agent with excellent high temperature resistance and wear resistance.

[0008] In order to solve at least one of the above problems, the present invention provides a method for preparing an FDY oil agent that can be directly oiled from crude oil, the preparation method comprising:

[0009] S100, according to the mass ratio of sizing agent: antistatic agent: emulsifier: phase change wear agent: smoothing agent = (4-8): (6-12): (20-25): (10-25): (50-80), add sizing agent, antistatic agent, emulsifier, phase change wear agent and smoothing agent into the reaction kettle;

[0010] S200, raising the temperature of the reactor to 40° C. to 60° C., turning on the stirring device of the reactor, and continuously stirring for 20 min to 40 min under the heat preservation condition to obtain FDY oil agent;

[0011] Wherein, the phase change wear-resistant agent is prepared by the following steps:

[0012] S310, using a raw material including paraffin to prepare an oil phase;

[0013] S320, using raw materials including ethyl orthosilicate to prepare an aqueous phase;

[0014] S330, preparing an emulsion using raw materials including polyol and isophorone diisocyanate;

[0015] S340, mixing the emulsion, the oil phase and the water phase, and preparing a phase change anti-wear agent through an oil-in-water emulsification system.

[0016] In any of the above technical solutions, S310 specifically includes:

[0017] First, ammonium thiocyanate and ammonium polyphosphate are uniformly mixed in water, and then Tween 60, dodecyl betaine and paraffin are added, and the mixture is heated in a water bath at 70° C. to 75° C. and vegetable oil is gradually added while stirring to obtain an oil phase.

[0018] In any of the above technical solutions, in S310, the mass ratio of Tween 60: dodecyl betaine: ammonium thiocyanate: ammonium polyphosphate: paraffin: water: vegetable oil is (1-2): (1-2): (4-6): (4-8): (30-40): (15-25): 100.

[0019] In any of the above technical solutions, S320 specifically includes:

[0020] The tetraethyl orthosilicate is stirred evenly in a mixture of ethanol and water, and cardanol polyoxyethylene ether phosphate is added continuously, and the mixture is stirred evenly again to obtain an aqueous phase.

[0021] In any of the above technical solutions, in S320, the mass ratio of cardanol polyoxyethylene ether phosphate:ethyl orthosilicate:ethanol:water=(4-6):(25-30):(30-35):100.

[0022] In any of the above technical solutions, S330 specifically includes:

[0023] S331, placing polycarbonate polyol and polyether polyol in a reaction vessel for vacuum dehydration;

[0024] S332, adding graphite and isophorone diisocyanate, and reacting at a temperature of 70° C. to 75° C. for 1.5 h to 2 h;

[0025] S333, adding trimethylolpropane and continuing the reaction at a temperature of 80° C. to 85° C. for 1.5 to 2.5 hours;

[0026] S334. After the reaction is completed, the pH value is adjusted to 6-7, cetyltrimethylammonium bromide and water are added and emulsified evenly, and the mixture is cooled to room temperature to obtain an emulsion.

[0027] In any of the above technical solutions, in S330, the mass ratio of trimethylolpropane: hexadecyltrimethylammonium bromide: graphite: isophorone diisocyanate: polycarbonate polyol: polyether polyol: water = (2-4): (2-4): (30-40): (40-60): (20-30): (80-100): 100.

[0028] In any of the above technical solutions, S340 specifically includes:

[0029] S341, placing the emulsion in a water bath at 38°C to 48°C, dropping the oil phase and the water phase into the emulsion simultaneously and stirring, and keeping the mixture warm and stirring for 4h to 6h after the addition is complete;

[0030] S342, continue to add sodium hydroxide aqueous solution to adjust the pH value to 11 to 12 while stirring, and continue stirring for 18 to 24 hours after the addition is completed;

[0031] S343, filter the solid, soak it in anhydrous ethanol for 24 hours to 30 hours, wash it, and dry it to obtain a phase change wear-resistant agent.

[0032] In any of the above technical solutions, in S340, the mass ratio of emulsion: oil phase: water phase = (60-80): (80-120): 100.

[0033] The present invention also provides an FDY oil agent that can be directly oiled from crude oil. The FDY oil agent that can be directly oiled from crude oil is obtained by using the preparation method of any of the above technical solutions.

[0034] Beneficial Effects

[0035] The present invention provides a method for preparing an FDY oil agent that can be directly oiled with crude oil. The FDY oil agent is mainly used in polyester production. As an indispensable auxiliary agent in the polyester spinning process, the fiber can have good smoothness, bundling and antistatic properties, thereby meeting the requirements of fiber processing. The preparation method of the present invention first puts a bundling agent, an antistatic agent, an emulsifier, a phase change wear-resistant agent and a smoothing agent into a reactor, heats the reactor to 40°C to 60°C, and turns on the stirring device of the reactor. Stir continuously for 20min to 40min under heat preservation conditions to obtain an FDY oil agent. The FDY oil agent is mainly used in polyester production. As an indispensable auxiliary agent in the polyester spinning process, the fiber can have good smoothness, bundling and antistatic properties, thereby meeting the requirements of fiber processing. Among them, the wear-resistant agent of the present invention is silicon dioxide, which has the characteristics of high mechanical strength, good thermal stability and wear resistance. In order to further increase the thermal stability of the FDY oil agent, it is prevented from coking in a high-temperature working environment, or the friction coefficient increases after working under long-term high-temperature conditions. The present invention compounds paraffin phase change material with silicon dioxide. Considering that the method of using silicon dioxide particles or porous silicon dioxide as the inner core and using paraffin to coat silicon dioxide to realize silicon dioxide loading paraffin is easy to cause paraffin to separate from silicon dioxide due to phase change under high temperature environment, thereby destroying the water-oil balance of the oil agent, causing the oil agent to demulsify or stratify, the present invention provides a wear-resistant agent obtained by a water-in-oil method with a wall material including nano-silicon dioxide coating a paraffin core material. Paraffin, as a core material coated with silicon dioxide, is not easy to lose, and the corresponding FDY oil agent is also not easy to demulsify or stratify during use. Silicon dioxide is coated outside the paraffin, which can give full play to the wear-resistant advantage. In addition, compared with the method of coating silica with paraffin wax, the dispersibility of silica in the liquid phase is not ideal when silica is used as the wall material. Considering this problem, the present invention mixes the polyurethane-containing emulsion with the paraffin oil phase and the silicon source water phase, thereby using polyurethane and silica sol to mix, thereby using polyurethane to improve the dispersion uniformity and storage stability of silica in liquid organic matter. In summary, the present invention can obtain an FDY oil agent with excellent high temperature resistance and wear resistance, and its performance is stable, easy to store, and not easy to stratify. DETAILED DESCRIPTION

[0036] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description of the specific embodiments of the present invention.

[0037] Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications.

[0038] FDY oil agent is mainly used in polyester production. It is an essential auxiliary agent in the polyester spinning process to ensure that polyester fibers have good smoothness, bundling and antistatic properties.

[0039] The present invention provides an FDY oil agent that can be directly oiled with crude oil, which is characterized by good high temperature resistance and wear resistance, and good storage stability. The preparation method of the FDY oil agent of the present invention comprises:

[0040] S100, according to the mass ratio of sizing agent: antistatic agent: emulsifier: phase change wear agent: smoothing agent = (4-8): (6-12): (20-25): (10-25): (50-80), add sizing agent, antistatic agent, emulsifier, phase change wear agent and smoothing agent into the reaction kettle;

[0041] S200, raising the temperature of the reactor to 40° C. to 60° C., turning on the stirring device of the reactor, and continuously stirring for 20 min to 40 min under the heat preservation condition to obtain FDY oil agent.

[0042] The purpose of the above steps is to prepare FDY oil by uniformly mixing the raw materials. In order to achieve uniform mixing, the raw materials are sent to a reactor and stirred for a certain period of time under the condition of heating. Wherein, the anti-wear agent of the present invention is a composite of silicon dioxide, phase change material and polyurethane. The present invention improves the anti-wear agent preparation process to prepare a silicon dioxide anti-wear agent with a wall material including nano silicon dioxide coated with a paraffin core material, which utilizes the phase change heat storage characteristics of the paraffin core material to protect the FDY oil, and avoids the FDY oil from coking, increasing the friction coefficient, demulsification and oil film rupture in a high-temperature working environment. In addition, the anti-wear agent of the present invention can be uniformly and stably dispersed in the FDY oil, so that the FDY oil is not easy to stratify after long-term storage.

[0043] Before introducing the modification process of the phase change wear-resistant agent, other raw materials used in the preparation process of the FDY oil are first explained. In the FDY oil of the present invention, the sizing agent is a chemical auxiliary agent used in the fiber material processing process, and its main function is to improve the cohesion between fibers, so that the fibers can be bundled into bundles, thereby increasing the load-bearing capacity and tensile strength of the fibers. Exemplarily, the sizing agent used in the present invention includes at least one of lauroyl diethanolamine, coconut oil diethanolamide, oleic acid triethanolamine, polyethylene glycol oleate, and polyethylene glycol laurate.

[0044] An antistatic agent is a chemical substance that can increase the conductivity of the surface of an object and prevent static electricity accumulation. Its main function is to increase the conductivity of the material surface so that static charge can be leaked in time to avoid static electricity from affecting production. Exemplarily, the antistatic agent used in the present invention includes at least one of lauryl alcohol polyoxyethylene ether potassium phosphate, secondary alkyl sodium sulfonate, and lauryl alcohol polyoxyethylene ether.

[0045] An emulsifier is a surfactant that contains both a hydrophilic group and a lipophilic group in its molecule. Its main function is to reduce the interfacial tension of the components in the mixed system, form a relatively strong film or double electric layer on the surface of the droplets, prevent the droplets from aggregating with each other, and thus maintain a uniform emulsion. Exemplarily, the emulsifier used in the present invention includes at least one of isomeric alcohol polyoxyethylene ether, anhydrous sorbitan fatty acid ester, polyethylene glycol fatty acid ester, castor oil polyoxyethylene ether, cardanol polyoxyethylene ether, and sodium lauryl alcohol ether sulfate.

[0046] The smoothing agent can significantly improve the smoothness of the tow, making the surface of the tow smoother and more delicate, and also helps to reduce the friction coefficient between the tows, thereby reducing the entanglement and knotting of the tows during the production process. Exemplarily, the smoothing agent used in the present invention includes at least one of mineral oil, white oil, vegetable oil, silicone oil, fatty alcohol oleate or polyol oleate.

[0047] It should be noted that those skilled in the art are capable of selecting and adjusting the specific raw materials and component contents of the sizing agent, antistatic agent, emulsifier and smoothing agent according to actual needs. The selection of the above raw materials and their components in the present invention is a preferred solution for the preparation process of the phase change wear-resistant agent of the present invention. The preparation process of the phase change wear-resistant agent of the present invention will be described below.

[0048] The wear-resistant agent used in the present invention comprises silicon dioxide, and is compounded with a paraffin phase change material and modified by polyurethane. The phase change wear-resistant agent used in the present invention is prepared by the following steps:

[0049] S310, using a raw material including paraffin to prepare an oil phase;

[0050] S320, using raw materials including ethyl orthosilicate to prepare an aqueous phase;

[0051] S330, preparing an emulsion using raw materials including polyol and isophorone diisocyanate;

[0052] S340, mixing the emulsion, the oil phase and the water phase, and preparing a phase change anti-wear agent through an oil-in-water emulsification system.

[0053] Paraffin phase change refers to the process in which paraffin is converted from solid to liquid or from liquid to solid during the heating or cooling process. In this process, paraffin absorbs or releases a large amount of heat, which is due to the need for its molecules to overcome or release internal energy during phase change. When paraffin is in a solid state, its molecules are in a relatively stable state, at which time the energy consumed is less and the temperature is relatively low. When the temperature gradually rises to the phase change temperature of paraffin, paraffin begins to convert from solid to liquid. In this process, paraffin absorbs a large amount of heat, which is called latent heat of phase change. The absorption of latent heat of phase change enables paraffin to effectively absorb and store the heat energy of the surrounding environment, thereby achieving an endothermic effect. In the above steps, paraffin, as a phase change material, acts to absorb heat in a high-temperature working environment to avoid coking and increased friction coefficient due to excessive temperature of FDY oil agent.

[0054] There are already some technical solutions in the prior art that utilize the phase change principle of paraffin (or other materials such as n-octadecane, n-nonadecane, etc.) to protect FDY oil at high temperatures. Since solid-liquid transitions occur during the phase change of paraffin, the paraffin material needs to be loaded on other carriers for use. These carriers are generally solid particles or inorganic non-metallic materials with loose porous structures. For example: porous silica and porous hydroxyapatite prepared by sol-gel method. Although filling or coating paraffin in porous materials can achieve paraffin loading, this method has a very limited load on paraffin, and paraffin coated outside the inorganic material is easy to liquefy in a high-temperature working environment and detach from the load carrier. When too much paraffin enters the solvent system of the oil, it will destroy the water-oil balance system of the oil, causing the oil to stratify and demulsify.

[0055] To this end, the technical solution of the present invention is to prepare the paraffin oil phase and the organic silicon source water phase separately, and then prepare the paraffin microcapsules by the water-in-oil method. The microcapsules use paraffin as the core material and nano-silicon dioxide formed by the sol-gel method as the wall material, so that the wall material is coated outside the core material, and the wear resistance and high temperature resistance of silicon dioxide are utilized. At the same time, silicon dioxide is used to protect the paraffin, and the liquefied paraffin in the high temperature working environment is prevented or restricted from entering the oil agent system too much, thereby avoiding stratification and demulsification of the oil agent.

[0056] In addition, considering that silica has poor dispersion performance in liquid systems (whether emulsion systems, water dispersions or oil dispersions), and that it is easy for the liquid system to stratify and precipitate due to agglomeration, the technical solution of the present invention further utilizes a water-soluble polyurethane emulsion to compound silica, thereby reducing the surface energy of silica, improving its compatibility with the organic phase and its dispersion stability in the liquid system.

[0057] In the technical solution of the present invention, S310 specifically includes:

[0058] First, ammonium thiocyanate and ammonium polyphosphate are uniformly mixed in water, and then Tween 60, dodecyl betaine and paraffin are added, and the mixture is heated in a water bath at 70° C. to 75° C. and vegetable oil is gradually added while stirring to obtain an oil phase.

[0059] In S310, the mass ratio of Tween 60: dodecyl betaine: ammonium thiocyanate: ammonium polyphosphate: paraffin: water: vegetable oil is (1-2): (1-2): (4-6): (4-8): (30-40): (15-25): 100.

[0060] Preferably, in S310, the mass ratio of Tween 60: dodecyl betaine: ammonium thiocyanate: ammonium polyphosphate: paraffin: water: vegetable oil is 1:2:4:6:35:15:100.

[0061] In the above steps, Tween 60 is used as an emulsifier, paraffin is used as a phase change thermal storage material, and vegetable oil is used as a solvent, and an oil phase dispersion system containing paraffin is obtained by stirring. The vegetable oil is preferably palm oil. Ammonium thiocyanate and ammonium polyphosphate are used as auxiliary phase change materials, which undergo chemical changes at a high temperature above 140°C and release flame-retardant gas, thereby further protecting the oil agent and preventing it from coking and smoking.

[0062] It can be understood that in the above steps, water-soluble ammonium thiocyanate and ammonium polyphosphate are first mixed and dissolved in water, and then the oily raw material is added and stirred. The purpose of stirring is, on the one hand, to make the raw materials uniformly mixed, and on the other hand, to emulsify the system so as to obtain a uniform dispersed system later. In order to achieve emulsification, the stirring speed of S310 is preferably 6000rpm / min to 8000rpm / min. Wherein, the degree of polymerization of ammonium polyphosphate is between 10 and 20.

[0063] In the technical solution of the present invention, S320 specifically includes:

[0064] The tetraethyl orthosilicate is stirred evenly in a mixture of ethanol and water, and cardanol polyoxyethylene ether phosphate is added continuously, and the mixture is stirred evenly again to obtain an aqueous phase.

[0065] In S320, the mass ratio of cardanol polyoxyethylene ether phosphate:ethyl orthosilicate:ethanol:water=(4-6):(25-30):(30-35):100.

[0066] Preferably, in S320, the mass ratio of cardanol polyoxyethylene ether phosphate:ethyl orthosilicate:ethanol:water=4:30:35:100.

[0067] Among them, cardanol polyoxyethylene ether phosphate is used as an emulsifier. The purpose of stirring in the above steps is also to make the raw materials evenly mixed on the one hand, and to emulsify the aqueous system under the action of the emulsifier on the other hand, so as to obtain a uniform dispersion system in the subsequent step. In order to achieve emulsification, the stirring speed of S320 is preferably 6000rpm / min to 8000rpm / min.

[0068] In the technical solution of the present invention, S330 specifically includes:

[0069] S331, placing polycarbonate polyol and polyether polyol in a reaction vessel for vacuum dehydration;

[0070] S332, adding graphite and isophorone diisocyanate, and reacting at a temperature of 70° C. to 75° C. for 1.5 h to 2 h;

[0071] S333, adding trimethylolpropane and continuing the reaction at a temperature of 80° C. to 85° C. for 1.5 to 2.5 hours;

[0072] S334. After the reaction is completed, the pH value is adjusted to 6-7, cetyltrimethylammonium bromide and water are added and emulsified evenly, and the mixture is cooled to room temperature to obtain an emulsion.

[0073] In S330, the mass ratio of trimethylolpropane: hexadecyltrimethylammonium bromide: graphite: isophorone diisocyanate: polycarbonate polyol: polyether polyol: water is (2-4): (2-4): (30-40): (40-60): (20-30): (80-100): 100.

[0074] Preferably, in S330 , in terms of mass ratio, trimethylolpropane: hexadecyltrimethylammonium bromide: graphite: isophorone diisocyanate: polycarbonate polyol: polyether polyol: water=2:4:30:50:20:100:100.

[0075] The purpose of the above steps is to prepare a waterborne polyurethane emulsion. Polyurethane needs to be obtained by reacting polyols and diisocyanates. Among them, polycarbonate polyols have good mechanical properties and can also give waterborne polyurethanes better heat resistance and friction resistance. The even carbon structure of polyether polyols can provide waterborne polyurethanes with better film-forming properties, which is conducive to a more uniform and tight compounding of polyurethane and silica.

[0076] It is understood that the polycarbonate polyol and the polyether polyol need to be vacuum dehydrated before the reaction, the vacuum dehydration temperature is preferably 90° C. to 110° C., and the vacuum dehydration time is preferably 1 h to 2 h. After the vacuum dehydration, isophorone diisocyanate can be added for reaction.

[0077] It should be noted that, before the reaction, the temperature of the mixture of polycarbonate polyol and polyether polyol needs to be lowered from 90° C. to 110° C. during vacuum dehydration to 70° C. to 75° C. before adding isophorone diisocyanate.

[0078] It is understood that in this reaction, a catalyst may be added to promote the reaction. The amount and type of the catalyst may be selected by a person skilled in the art according to actual needs. Preferably, the catalyst is selected from any one of BiCAT 8118, BiCAT 8108, BiCAT 8124, BiCAT 8106, Borchi Kat 22, and Borchi Kat 24, and the amount of the catalyst added is 0.1% to 0.2% of the mass of isophorone diisocyanate.

[0079] It is understood that trimethylolpropane can be added directly or dissolved in a solvent such as acetone before adding. The role of trimethylolpropane is to act as a chain extender to induce a chain extension reaction.

[0080] It can be understood that the time of the chain extension reaction is within the range of 1.5 h to 2.5 h. The specific time can be determined by those skilled in the art based on the detection of the NCO content in the system. The reaction can be terminated when the NCO content in the system reaches the theoretical value.

[0081] The technical solution of the present invention adds graphite in the preparation process of waterborne polyurethane. Graphite has good lubricity and thermal stability, and its thermal conductivity is good. After the polyurethane in which the graphite material is evenly dispersed is compounded with silicon dioxide, the graphite can promote the conduction of heat to the paraffin core material in a high-temperature working environment, so that the paraffin can more efficiently play the role of heat storage and high-temperature protection. Preferably, the graphite used in the present invention is a powder with an average diameter of 60 μm to 80 μm.

[0082] Considering that the lamellar structure makes graphite easy to agglomerate, the present invention uses hexadecyltrimethylammonium bromide to intercalate the graphite. Hexadecyltrimethylammonium bromide can make the graphite overcome the interlayer adhesion, increase the interlayer spacing of the graphite and peel off the layers, thereby improving the dispersion stability and uniformity of the graphite in the liquid phase.

[0083] In the technical solution of the present invention, S340 specifically includes:

[0084] S341, placing the emulsion in a water bath at 38°C to 48°C, dropping the oil phase and the water phase into the emulsion simultaneously and stirring, and keeping the mixture warm and stirring for 4h to 6h after the addition is complete;

[0085] S342, continue to add sodium hydroxide aqueous solution to adjust the pH value to 11 to 12 while stirring, and continue stirring for 18 to 24 hours after the addition is completed;

[0086] S343, filter the solid, soak it in anhydrous ethanol for 24 hours to 30 hours, wash it, and dry it to obtain a phase change wear-resistant agent.

[0087] In S340, the mass ratio of emulsion: oil phase: water phase = (60-80): (80-120): 100.

[0088] Preferably, in S340, the mass ratio of emulsion: oil phase: water phase is 60:90:100.

[0089] The above sodium hydroxide aqueous solution is a 4wt% to 10wt% sodium hydroxide aqueous solution. The above washing is performed once with a mixture of water and petroleum ether with a 30wt% petroleum ether content, and then washed twice with deionized water. Drying is preferably infrared drying at 80°C to 100°C.

[0090] As a cationic surfactant, hexadecyltrimethylammonium bromide can interact with graphite that is negatively charged in a neutral solution through electrostatic action, which not only improves the dispersion stability of graphite in polyurethane, but also gives graphite cationic properties. Since the paraffin oil phase contains dodecyl betaine that is anionic in an alkaline medium, after the paraffin oil phase and the silicon source water phase are simultaneously added to the polyurethane emulsion and stirred, the pH value is adjusted to 11 to 12 by adding sodium hydroxide aqueous solution. Sodium hydroxide can be used as a catalyst to form a silica sol in the reaction system, and the anionic properties of dodecyl betaine under alkaline conditions can be used to make the graphite modified by hexadecyltrimethylammonium bromide and having cationic properties electrostatically attract each other with the paraffin core material, forming a structure in which graphite particles surround the paraffin core material, achieving a better thermal conductivity effect. It can be understood that the purpose of heat preservation and stirring in S341 is to fully emulsify the system, and the stirring speed of S341 is preferably 4000rpm / min to 8000rpm / min. In the present invention, since an emulsifier is added to the water phase, and after the emulsion, oil phase, and water phase are uniformly mixed and emulsified, sodium hydroxide is added dropwise to induce the sol-gelation of silicon dioxide and the electrostatic attraction of graphite and paraffin wax, the above steps can obtain water-in-oil microcapsules, whose core material is paraffin wax, and the wall material is a film layer formed by a composite of polyurethane, graphite, and nano-silicon dioxide. Silicon dioxide coats and protects the paraffin wax, and after the polyurethane and silicon dioxide are composited, the wall material becomes more uniform and dense, and the compatibility with the organic phase is improved. The graphite is uniformly coated around the paraffin wax under the action of electrostatic attraction, which promotes the conduction of heat and improves the phase change heat storage and high temperature protection effect of the paraffin wax.

[0091] Embodiment 1

[0092] In this embodiment, a phase change wear-resistant agent sample 1 is prepared, and its specific preparation process is as follows.

[0093] S1. According to the mass ratio of Tween 60: dodecyl betaine: ammonium thiocyanate: ammonium polyphosphate: paraffin: water: palm oil = 1:2:4:6:35:15:100, first dissolve ammonium thiocyanate and ammonium polyphosphate with a degree of polymerization of 10 to 20 in water and mix them evenly, then add Tween 60, dodecyl betaine and paraffin, heat in a water bath at 70°C and gradually add palm oil, and stir at a speed of 6000 rpm / min for 30 minutes to obtain an oil phase;

[0094] S2. According to the mass ratio of cardanol polyoxyethylene ether phosphate:ethyl orthosilicate:ethanol:water=4:30:35:100, ethyl orthosilicate is uniformly stirred at a speed of 500 rpm / min in a mixture of ethanol and water, cardanol polyoxyethylene ether phosphate is continuously added, and the mixture is stirred again at a speed of 6000 rpm / min for 20 min to obtain an aqueous phase;

[0095] S3. First, polycarbonate polyol and polyether polyol are placed in a reaction vessel at a temperature of 90° C. to 110° C. for vacuum dehydration for 2 h according to a mass ratio of trimethylolpropane: hexadecyltrimethylammonium bromide: graphite: isophorone diisocyanate: polycarbonate polyol: polyether polyol: water = 2:4:30:50:20:100:100, and then the temperature is reduced to 70° C., graphite and isophorone diisocyanate, as well as BiCAT 8118 catalyst added in an amount of 0.1% of the mass of isophorone diisocyanate, and reacted at a temperature of 70° C. until the NCO content in the system reaches the theoretical value (about 2 h), and then trimethylolpropane is added and the reaction is continued at a temperature of 80° C. for 2 h. After the reaction, hexadecyltrimethylammonium bromide and water are added and ultrasonic emulsification is performed at a power of 400 W for 30 min, and the temperature is cooled to room temperature to obtain an emulsion;

[0096] S4. According to the mass ratio of emulsion: oil phase: water phase = 60:90:100, first place the emulsion in a water bath at 38°C, then simultaneously drop the oil phase and water phase into the emulsion and stir. After the addition is completed within 1.5 hours, keep warm and stir for 4 hours, continue to drop 8wt% sodium hydroxide aqueous solution to adjust the pH value to 12 and stir at a speed of 500rpm / min. After the addition is completed, continue to stir for 20 hours, filter the solids, soak in anhydrous ethanol for 24 hours, wash once with a mixture of water and petroleum ether with a petroleum ether content of 30wt%, and then wash twice with deionized water, and infrared drying at 90°C to obtain phase change wear-resistant agent sample 1.

[0097] Embodiment 2

[0098] In this embodiment, a phase change wear-resistant agent sample 2 is prepared, and its specific preparation process is as follows.

[0099] S1. Dissolve ammonium thiocyanate and ammonium polyphosphate with a degree of polymerization of 10 to 20 in water according to a mass ratio of Tween 60: ammonium thiocyanate: ammonium polyphosphate: paraffin: water: palm oil = 1:4:6:35:15:100 and mix them evenly, then add Tween 60 and paraffin, heat in a water bath at 70°C and gradually add palm oil, and stir at a speed of 6000 rpm / min for 30 minutes to obtain an oil phase;

[0100] S2. According to the mass ratio of cardanol polyoxyethylene ether phosphate:ethyl orthosilicate:ethanol:water=4:30:35:100, ethyl orthosilicate is uniformly stirred at a speed of 500 rpm / min in a mixture of ethanol and water, cardanol polyoxyethylene ether phosphate is continuously added, and the mixture is stirred again at a speed of 6000 rpm / min for 20 min to obtain an aqueous phase;

[0101] S3. First, polycarbonate polyol and polyether polyol are placed in a reaction vessel at a temperature of 90° C. to 110° C. for vacuum dehydration for 2 h according to a mass ratio of trimethylolpropane: graphite: isophorone diisocyanate: polycarbonate polyol: polyether polyol: water = 2:30:50:20:100:100, and then the temperature is reduced to 70° C., graphite and isophorone diisocyanate, as well as BiCAT 8118 catalyst added in an amount of 0.1% of the mass of isophorone diisocyanate, and reacted at a temperature of 70° C. until the NCO content in the system reaches the theoretical value (about 2 h), and then trimethylolpropane is added and the reaction is continued at a temperature of 80° C. for 2 h. After the reaction is completed, water is added and ultrasonic emulsification is performed at a power of 400 W for 30 min, and the temperature is cooled to room temperature to obtain an emulsion;

[0102] S4. According to the mass ratio of emulsion: oil phase: water phase = 60:90:100, first place the emulsion in a water bath at 38°C, then simultaneously drop the oil phase and water phase into the emulsion and stir. After the addition is completed within 1.5 hours, keep warm and stir for 4 hours, continue to drop 8wt% sodium hydroxide aqueous solution to adjust the pH value to 12 and stir at a speed of 500rpm / min. After the addition is completed, continue to stir for 20 hours, filter the solids, soak in anhydrous ethanol for 24 hours, wash once with a mixture of water and petroleum ether with a petroleum ether content of 30wt%, and then wash twice with deionized water. Dry at 90°C with infrared drying to obtain phase change wear-resistant agent sample 2.

[0103] Embodiment 3

[0104] In this embodiment, a phase change wear-resistant agent sample 3 is prepared. Its raw materials and specific preparation process are basically the same as those in Example 1. The only difference is that in S4, after the oil phase and the water phase are added dropwise and stirred for 4 hours, a hydrochloric acid aqueous solution with a pH of 2 is continued to be added dropwise to adjust the pH value of the system to 4 and stirred at a speed of 500 rpm / min simultaneously. After the addition is completed, the stirring, filtering, ethanol soaking, washing and drying steps are the same as those in Example 1 to obtain a phase change wear-resistant agent sample 3.

[0105] Embodiment 4

[0106] In this embodiment, a phase change wear-resistant agent sample 4 is prepared, and the raw materials and specific preparation process of the oil phase and the water phase are the same as those of the embodiment 1, except that the emulsion prepared in this embodiment does not contain graphite. The preparation process of the emulsion is as follows: according to the mass ratio of trimethylolpropane: isophorone diisocyanate: polycarbonate polyol: polyether polyol: water = 2: 50: 20: 100: 100, firstly place the polycarbonate polyol and the polyether polyol in a reaction vessel at a temperature of 90°C to 110°C for vacuum dehydration for 2h, then cool to 70°C, add isophorone diisocyanate, and add BiCAT 8118 catalyst in an amount of 0.1% of the mass of isophorone diisocyanate, and react at a temperature of 70°C until the NCO content in the system reaches the theoretical value (about 2h), then add trimethylolpropane and continue to react at a temperature of 80°C for 2h, add water after the reaction is completed, and ultrasonically emulsify at a power of 400W for 30min, cool to room temperature, and obtain an emulsion. After obtaining the emulsion, the emulsion, oil phase and water phase are mixed, stirred at a constant temperature, alkali is added to adjust the pH value, stirring is continued, filtered, ethanol soaked, washed and dried in the same manner as in Example 1 to obtain a phase change wear-resistant agent sample 4.

[0107] Embodiment 5

[0108] Phase change wear-resistant agent sample 5 was prepared in this embodiment. The raw materials and specific preparation process of the oil phase and water phase were the same as those in embodiment 1. The difference was that the polyurethane emulsion was not prepared in this embodiment, but the oil phase and water phase were directly mixed. After the oil phase and water phase were prepared separately by the process of embodiment 1, the oil phase was gradually added to the water phase with a mass ratio of oil phase: water phase = 90:100 and stirred. After the addition was completed, the mixture was kept warm and stirred for 4 hours. The steps of adding alkali to adjust the pH value, continuing stirring, filtering, ethanol soaking, washing and drying were the same as those in embodiment 1 to obtain phase change wear-resistant agent sample 5.

[0109] Embodiment 6

[0110] In this example, a series of FDY oil samples 1 to 5 were prepared. The raw material components used in the preparation process of the FDY oil are shown in Table 1, and the specific preparation process is as follows.

[0111] With the sources of phase change wear-resistant agent in Table 1, coconut oil diethanolamide sizing agent, lauryl alcohol polyoxyethylene ether antistatic agent, isomeric alcohol polyoxyethylene ether emulsifier, phase change wear-resistant agent and smoothing agent white oil were put into the reactor according to the mass ratio of sizing agent: antistatic agent: emulsifier: phase change wear-resistant agent: smoothing agent = 4:10:20:10:56; the reactor was evacuated and heated to 50°C, and the stirring device of the reactor was turned on. Stirring was continued for 40 minutes under insulation conditions to obtain FDY oil.

[0112] Table 1

[0113]

[0114] Performance Testing

[0115] The performance parameters of FDY oil samples 1 to 5 are shown in Table 2. Among them, the dynamic friction coefficient and oiling rate are obtained by using FDY oil samples 1 to 5 on the spinning position under the same conditions for 15 days and 25 days, the spinning speed is 4800m / min, and the GR2 temperature is 135℃. The detection method of smoke emission is to weigh 10g of sample and place it in a 50ml beaker, place the beaker in an electric heating jacket for continuous heating, and observe its smoke emission. The detection method of coking property is to measure 1.0ml of sample and drop it on the steel sheet, place the steel sheet in an oven at 220℃ for heating treatment for 3min, and observe the coking performance of the sample after cooling to 25℃. The detection method of volatile reduction is to take 2g of sample and place it in a 50ml beaker, place the beaker in an oven at 200℃ for heating treatment for 2h, cool to 25℃, weigh and calculate the volatile amount of the sample. The detection method of open flash point is carried out in accordance with GB / T3536.

[0116] The above test results show that the FDY oil obtained by the technical solution of the present invention has stable performance, small friction coefficient, longer lubrication effect and longer service life under high temperature conditions after long-term use. In addition, the addition of graphite and the uniform coating of graphite on paraffin can increase the service life of the FDY oil in a long-term high-temperature use environment.

[0117] Table 2

[0118]

[0119] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing an FDY oil agent that can be directly oiled from crude oil, characterized in that: The preparation method comprises: S100, according to the mass ratio of sizing agent: antistatic agent: emulsifier: phase change wear-resistant agent: smoothing agent = (4-8): (6-12): (20-25): (10-25): (50-80), the sizing agent, the antistatic agent, the emulsifier, the phase change wear-resistant agent and the smoothing agent are added into a reaction kettle; S200, raising the temperature of the reactor to 40° C. to 60° C., turning on the stirring device of the reactor, and continuously stirring for 20 min to 40 min under the heat preservation condition to obtain the FDY oil solution; Wherein, the phase change wear-resistant agent is prepared by the following steps: S310, using a raw material including paraffin to prepare an oil phase; S320, using raw materials including ethyl orthosilicate to prepare an aqueous phase; S330, preparing an emulsion using raw materials including polyol and isophorone diisocyanate; S340, mixing the emulsion, the oil phase and the water phase to prepare a phase change anti-wear agent through an oil-in-water emulsification system; S330 specifically includes: S331, placing polycarbonate polyol and polyether polyol in a reaction vessel for vacuum dehydration; S332, adding graphite and the isophorone diisocyanate, and reacting at a temperature of 70° C. to 75° C. for 1.5 h to 2 h; S333, adding trimethylolpropane and continuing the reaction at a temperature of 80° C. to 85° C. for 1.5 to 2.5 hours; S334, after the reaction is completed, the pH value is adjusted to 6-7, cetyltrimethylammonium bromide and water are added and emulsified evenly, and the mixture is cooled to room temperature to obtain the emulsion; S310 specifically includes: First, ammonium thiocyanate and ammonium polyphosphate are uniformly mixed in water, and then Tween 60, dodecyl betaine and the paraffin are added, and the mixture is heated in a water bath at 70° C. to 75° C. and vegetable oil is gradually added while stirring to obtain the oil phase; S340 specifically includes: S341, placing the emulsion in a water bath at 38° C. to 48° C., adding the oil phase and the water phase to the emulsion simultaneously and stirring, and keeping the temperature and stirring for 4 h to 6 h after the addition is completed; S342, continue to add sodium hydroxide aqueous solution to adjust the pH value to 11 to 12 while stirring, and continue stirring for 18 to 24 hours after the addition is completed; S343, filtering the solid, soaking it in anhydrous ethanol for 24 hours to 30 hours, washing it, and drying it to obtain the phase change wear-resistant agent.

2. The preparation method according to claim 1, characterized in that: In S310, the mass ratio of Tween 60: dodecyl betaine: ammonium thiocyanate: ammonium polyphosphate: paraffin: water: vegetable oil is (1-2): (1-2): (4-6): (4-8): (30-40): (15-25):

100.

3. The preparation method according to claim 1, characterized in that: S320 specifically includes: The ethyl orthosilicate is stirred evenly in a mixture of ethanol and water, and cardanol polyoxyethylene ether phosphate is added continuously, and stirred evenly again to obtain the aqueous phase.

4. The preparation method according to claim 3, characterized in that: In S320, the mass ratio of cardanol polyoxyethylene ether phosphate:ethyl orthosilicate:ethanol:water=(4-6):(25-30):(30-35):

100.

5. The preparation method according to claim 1, characterized in that: In S330, the mass ratio of trimethylolpropane: hexadecyltrimethylammonium bromide: graphite: isophorone diisocyanate: polycarbonate polyol: polyether polyol: water is (2-4): (2-4): (30-40): (40-60): (20-30): (80-100):

100.

6. The preparation method according to claim 1, characterized in that: In S340, the mass ratio of emulsion: oil phase: water phase = (60-80): (80-120):

100.

7. An FDY oiling agent that can be directly oiled with crude oil, characterized in that: The FDY oil agent that can be directly oiled from crude oil is obtained by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Polyester POY (polyester pre-oriented yarn) oiling agent and preparation method thereof

    CN116556056A

  • FDY (fully drawn yarn) crude oil type oiling agent for polyester fibers and preparation method thereof

    CN118835352A

Cited By

  • Polyester FDY (fully drawn yarn) oiling agent with high thermal stability, antistatic property and wear resistance and preparation method of polyester FDY oiling agent

    CN120591921A

  • High-heat-stability, antistatic and wear-resistant polyester fdy oil and its preparation method

    CN120591921B